Konsep Pendidikan Islam Al-Zarnuji (Telaah Kitab Ta’lim Al-Muta’allim) - Muhammad Fathurrahman (Tafhim Al-'Ilmi, 2015)
The concept of Islamic education according to al-Zarnuji an integrative educational concept which is filled with Islamic values. Educators are components that must exist in Islamic education, work becomes an educator is a noble job as educators to educate the soul learners. Learners according to al-Zarnuji, is how people learn. The purpose of education is to get closer to God and attain happiness in this world and the hereafter, seeking to combat ignorance in yourself and the stupid, develop and preserve Islam, ingratitude mind and a healthy body. The learning process according to al-Zarnuji within the limits of the interaction between teachers and students in the transfer of knowledge. Al-Zarnuji, in matters of curriculum, classify science into 4 types. In terms of method, al-Zarnuji initially proposed using rote methods followed with understanding. AbstrakKonsep pendidikan Islam menurut al-Zarnuji merupakan konsep pendidikan integratif yang penuh dengan nilai-nilai keislaman. Pendidik adalah komponen yang harus ada dalam pendidikan Islam, pekerjaan menjadi seorang pendidik merupakan pekerjaan yang mulia karena pendidik mendidik jiwa peserta didik. Peserta didik menurut al-Zarnuji, adalah manusia yang belajar. Tujuan pendidikan adalah untuk mendekatkan diri kepada Allah dan mencapai kebahagiaan di dunia dan akhirat, berusaha memerangi kebodohan pada diri sendiri dan kaum yang bodoh, mengembangkan dan melestarikan Islam, mensyukuri nikmat akal dan badan yang sehat. Proses pembelajaran menurut al-Zarnuji dalam batasan interaksi antara guru dan murid dalam transfer keilmuan. Al-Zarnuji, dalam masalah kurikulum, mengklasifikasikan ilmu pengetahuan menjadi 4 macam. Dalam hal metode, al-Zarnuji mengemukakan mula-mula menggunakan metode hafalan kemudian dilanjutkan dengan pemahaman.